ANALISIS PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP MINAT BELI SMARTPHONE ADVAN MELALUI CITRA MEREK SEBAGAI VARIABEL INTERVENING DI WILAYAH YOGYAKARTA - Mbajeng Prastiyani; Suhartono Suhartono (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2020)
This study aims to determine (1) the effect of price and product quality on Advan smartphone brand image, (2) the effect of price and product quality on Advan smartphone buying interest, (3) the effect of brand image on buying interest, (4) influence of price and quality products for the interest in buying Advan smartphone through brand image as an intervening variable in the region of Yogyakarta. The population of this study is consumers or who have used or learned about Advan smartphones. Sampling is done using purposive sampling. The research data was obtained by collecting questionnaires about price, product quality, brand image and buying interest for 200 respondents. The analysis technique used for this research is Intervening Variable Regression Analysis with Path Analysis using IBM SPSS Statistics 20. These results indicate that (1) prices do not have a significant effect on brand image, (2) product quality has a significant and positive effect on brand image, (3) price is not significantly related to buying interest, (4) product quality has a significant and positive influence on interest buy, (5) brand image significant and positive influence on buying interest, (6) brand image does not intervene in the interest of prices against buying interest, (7) brand image is interfered with the influence of product quality on buying interest.